Frequency of Low Back Pain and Its Association with Functional Ability in Engineers: Low Back Pain and its Association with Functional Ability - Naz, Somiya; Talha, Muhammad; Nazir, Pervisha; Talat, Sabahat; Raza khan, Hassan; Shahid, Hamza (Pakistan Journal of Health Sciences, 2023)
Low back pain (LBP) is the most common health problem among workers; most workers experience this issue during their lives. There are some psycho-social factors interlinked with LBP including hostile work environments, long working hours & overtime working hours. Objective: To determine the frequency of low back pain in engineers and to evaluate the association between functional ability and low back pain in engineers. Methods: A descriptive Cross-Sectional study was conducted, and the data were collected through a convenient sampling technique from Rawalpindi, Islamabad, and Malakand. The duration of the study was 6 months after synopsis approval. Data collection were done using a self-structured questionnaire containing demographic data and clinical characteristics. Visual analogue scale for pain (VAS pain) and Back pain functional scale (BPFS) were used to assess pain and functional abilities. Results: There were 85.9% Males and 24.1% females in this study. The point prevalence of LBP was 36.7% and the 12-month prevalence was 63.3%. There was a moderate association found between the severity of LBP and functional ability [(r= -0.59), p < 0.001]. Conclusions: The study concluded that the prevalence of LBP is found in engineers. A moderately significant association was found between the severity of LBP and functional ability in engineers.